Perancangan Interior House of Lego di Surabaya - Rudy Putra Setyantara; Hedy Constancia Indrani; Hendy Mulyono (Intra, 2018)
Indonesia is one of the countries where the Lego sales its products. It starts to develop in recent years and make the children like it. Lego enthusiasts in Indonesia come from not just the children but also the adults. The Lego lovers need a facility that let them explore creativity and learn more through Lego. This need backgrounds the design of House of Lego in Surabaya. The atmosphere created by this design is based on the Playhouse of Creativity concept which is comfortable, relaxing, and fun. This design can also sharp the children and adults creativity.